The Influence of Generative Learning Strategies and Group Investigation on Students' Mathematical Communication Ability - Sartika, Dewi; Rahmaini; Siregar, Tanti Jumaisyaroh (Mahir : Jurnal Ilmu Pendidikan dan Pembelajaran, 2023)
This study aims to determine students' mathematical communication skills by using generative learning strategies and Group Investigation strategies in Mathematics in class VIII of MTs Swasta Al-Washliyah 55 Serbelawan. This study uses a quantitative research approach with quasi-experimental methods while data collection is carried out using test, interview and observation techniques. The subjects in this study were students of grades VIII-A and VIII-C of MTs Swasta Al-Washliyah 55 Serbelawan. Hypothesis testing with T Test and Analysis of Variance. The results of these findings are: 1) There is an effect of generative learning strategies on students' mathematical communication skills in class VIII MTs Swasta Al-Washliyah 55 Serbelawan. Based on the results of the T test analysis, the value of t count = 21,846 and the value of t table at the level (α=0.05) = 2.052, then t count > t table; 2) There is an effect of the group investigation learning strategy on students' mathematical communication skills in class VIII MTs Swasta Al-Washliyah 55 Serbelawan. Based on the results of the t test analysis, the value of t count = 24,363 and the value of t table at the level (α=0,05 ) = 2,052, then t count > t table; 3) There is no effect of generative learning strategies and group investigation strategies on mathematical communication skills in class VIII mathematics at MTs Swasta Al-Washliyah 55 Serbelawan. Based on the results of the analysis of the F test, the value of F count = 0.018 and the value of F table at the level (α=0.05) = 4.020, then F count < F table.